Gene mutation and surgical technique: suggestion or more? - Kawaguchi, Yoshikuni (Surg Oncol, 2019)
Advancements in chemotherapy and molecular targeted therapy have improved long-term outcomes for patients with resectable colorectal liver metastases (CLM). RAS mutation status was an original focus as a molecular biomarker as it predicted treatments response to anti-epidermal growth factor receptor agents. More recently, studies have incorporated somatic mutation data in analyses pertaining to surgical outcomes and prognosis. This evidenced-based review covers the implications of somatic mutations in patients undergoing resection of CLM.